Sistem Informasi Penjualan Sembako Berbasis Web pada Badan Usaha Milik Desa (BUMDES) Poto Bo’o Desa Wolotopo - Mariana Dewi Sartika Mbu; Kristianus Jago Tute; Elvira Esperanza Sala (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The rapid development of information technology requires adaptation across various business sectors, including small and medium enterprises (SMEs). BUMDes Poto Bo’o, located in Wolotopo Village, Ndona Timur District, still manages sales data manually using ledger books. This practice leads to several issues, such as data inaccuracies, lack of automatic inventory updates, and delays in report generation.This study aims to design and implement a basic necessities (sembako) sales information system for the BUMDes. The system development method used is the waterfall model, which consists of requirement analysis, system design, implementation, testing, and maintenance stages. The system is developed using PHP programming language and MySQL database.The main features of the system include product management, customer management, transaction processing, tracking of incoming and outgoing goods, and real-time sales reporting. The results show that the developed information system improves transaction recording accuracy, enhances inventory data accuracy, and accelerates the sales reporting process.Therefore, the system is expected to improve the operational efficiency of BUMDes Poto Bo’o, support financial management transparency, and increase public trust in the performance of the village-owned enterprise.